2021
DOI: 10.11157/anzswj-vol33iss3id893
|View full text |Cite
|
Sign up to set email alerts
|

Defining, teaching, and practising diversity: Another hegemonic discourse?

Abstract: INTRODUCTION: Respect for diversity is a primary principle of the social work profession; however, the term diversity has been critiqued as meaningless and is often linked with cultural competence. Gaps in terminology, education, and knowledge about how to practise diversity have been identified in health and social practice literature, while attempts to teach diversity have uncertain results. The research question guiding this master’s study was “What are the factors that inform Aotearoa social workers’ pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Traditional methodologies for understanding why and how leadership and Aoteaora New Zealand with experienced social workers, when asked how they engage with diversity in their practice, they identified that for them, the term diversity often gets in the way of practice. Yet engagement with diversity is a competency they are required to "tick off" annually (Beaumont, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methodologies for understanding why and how leadership and Aoteaora New Zealand with experienced social workers, when asked how they engage with diversity in their practice, they identified that for them, the term diversity often gets in the way of practice. Yet engagement with diversity is a competency they are required to "tick off" annually (Beaumont, 2018).…”
Section: Discussionmentioning
confidence: 99%